CMTV‐like ranavirus infection associated with high mortality in captive catfish‐like loach, Triplophysa siluorides, in China. Issue 3 (13th January 2020) - Deng, Lishuang; Geng, Yi; Zhao, Ruoxuan; Gray, Matthew J.; Wang, Kaiyu; Ouyang, Ping; Chen, Defang; Huang, Xiaoli; Chen, Zhengli; Huang, Chao; Zhong, Zhijun; Guo, Hongrui; et al.
Abstract: Ranaviruses are important emerging pathogens of ectothermic vertebrates that threaten aquaculture and wildlife worldwide. A mortality event occurred in a cultured population of catfish‐like loach ( Triplophysa siluorides ) in Sichuan Province, China. Gross clinical signs of the affected fish included skin lesions and haemorrhagic ulcers, which are often associated with ranaviruses. Inoculation of liver, kidney and spleen tissue homogenates in epithelioma papulosum cyprini (EPC) cells at 25°C resulted in cytopathic effect within 24 hr. Transmission electron microscopy of infected EPC cells revealed hexagonal viral arrays in the cytoplasm and icosahedral geometry of the virions. Following exposure of T. siluroides to the isolated virus, similar clinical signs were observed and the fish experienced 40% and 90% mortality after 21 days at 10 3.58 and 10 7.8 TCID50 /0.1 ml doses, respectively, providing evidence the isolated virus was the main causative agent of the mortality event. Diagnostic PCR of the major capsid protein gene of ranavirus showed that all samples of diseased fish and isolated virus were positive. Phylogenetic analysis revealed that the isolated virus, designated as FYLl40220, was associated with the Common Midwife Toad Virus (CMTV)‐like ranavirus clade. To our knowledge, this case represents the first report of CMTV‐associated mortality in a fish species. Collectively, these results suggest that the host range of CMTV‐like ranaviruses is greater than previously thought, and this clade of ranaviruses could have significant economic and biodiversity impacts.